ANALISIS RESPON HARGA SAHAM TERHADAP PENGUMUMAN LABA KUARTAL INTERIM DAN KUARTAL KEEMPAT - RATIH HANDAYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2003)
This research examines cross-quarter differences in the response of stock prices to earnings announcements. The research focuses on whether fourth quarter earnings announcements contain more or less information than those of interim quarters. Like many prior studies, this paper provides information about regressions of unexpected announcement period returns on measure of unexpected earnings. It conducted with three different measures of measures of unexpected earnings; earnings expectations are based on seasonal random walk, random walk with trend and market-adjusted trend. Using 45 firms and 720 quarterly earnings for period 1996 through 1999 with weighted last square, this paper present evidence that stock prices respond less to fourth quarter earnings announcements that to intern announcements. Fourth quarter announcement are characterized by a smaller ERC (Mandenhall and Nichols,1988; Salamon and Stober, 1994 and Lee and Park, 2000) and a lower explanatory power of unexpected earnings than earlier quarter announcements (Hagerman, Zmijewski and Shah, 1984) because of lower predictability of fourth quarter earnings (Collins, Hopwood and McKeown, 1984). This results suggests that fourth quarter earnings are less persistent and less useful to investors than interim quarter earnings. Two explanations from previous studies are the existence of fiscal year-and discretionary accruals from earnings management or the phenomenon of fourth quarter settling up described by Collins, Hopwood and McKeown (1984). In addition, measurement error in earning expectations may be larger in fourth quarters than in interim quarters (Salamon and Stober,1994)